A conserved tripeptide sorts proteins to peroxisomes (The Rockefeller University Press, 1989)
The firefly luciferase protein contains a peroxisomal targeting signal at its extreme COOH terminus (Gould et al., 1987). Site-directed mutagenesis of the luciferase gene reveals that this peroxisomal targeting signal consists of the COOH-terminal three amino acids of the protein, serine-lysine-leucine. When this tripeptide is appended to the COOH terminus of a cytosolic protein (chloramphenicol acetyltransferase), it is sufficient to direct the fusion protein into peroxisomes. Additional mutagenesis experiments reveal that only a limited number of conservative changes can be made in this tripeptide targeting signal without abolishing its activity. These results indicate that peroxisomal protein import, unlike other types of transmembrane translocation, is dependent upon a conserved amino acid sequence.